Missionary Writings on City Image of Chengdu in Late Qing Dynasty and Early Republican Days - TANG, Dongmei; LIU, Hongyu (Journal of Research for Christianity in China (JRCC), 2024)
In the second half of 19th century and the first half of the 20th century, missionaries from English-speaking world went into Sichuan area with missionary purpose. During their stay in Sichuan, they carefully observed Sichuan society and put their observations and thinking into writings. Chengdu was the center of their missionary work and thus had been richly depicted in these writings. This article sorts out missionaries’ writings on the city image of Chengdu during this period of time and by examining vocabularies and themes in these writings, points out that missionaries’ depiction composed a positive city image of Chengdu, therefore sets the image construction of Chengdu city apart from the negativity shown in most missionary writings on China and Chinese people during that period of time.